1983
DOI: 10.1530/acta.0.1030125
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ovarian oestrogens and in plasma gonadotrophins in female rabbits from birth to adulthood

Abstract: Plasma oestrogens (E1, E2) and gonadotrophins, and ovarian oestrogens, were determined in female rabbits from birth to 6 months. Increases in ovarian weight followed a curvilinear pattern, with a phase of slow growth (from 1 to 60 days) preceding a phase of rapid growth (from 60 to 90 days). At birth, E2 was already quantifiable in ovaries; it remained at very low levels up to 50 days. Ovarian E2 content increased until 6 months with two sharp rises between 50 days (46 \ m=+-\4 pg/2 ovaries) and 60 days (365 \… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…23,24 That extragonadal or nonestrogenic factors may contribute to sex differences in repolarization is suggested by the persistence of sex-related differences in AP after gonadectomy. Consistent with other reports, 7,8 however, our results demonstrate that gonadal steroids modulate proarrhythmic responses to I Kr blockers.…”
Section: Effects Of Gonadectomy and Hormone Replacementmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 That extragonadal or nonestrogenic factors may contribute to sex differences in repolarization is suggested by the persistence of sex-related differences in AP after gonadectomy. Consistent with other reports, 7,8 however, our results demonstrate that gonadal steroids modulate proarrhythmic responses to I Kr blockers.…”
Section: Effects Of Gonadectomy and Hormone Replacementmentioning
confidence: 99%
“…Their serum estradiol levels remain constant and low (Ͻ100 pg/mL) and are unchanged by oophorectomy. 23 In women, normal estradiol levels range from 130 to 400 pg/mL. 30 Thus, the oophorectomized rabbit model fails to replicate the differences in estradiol levels between normal premenopausal and postmenopausal women.…”
Section: Limitationsmentioning
confidence: 99%
“…As part of our continuing studies to elucidate the mechanisms by which female rabbits become sexually mature, we have observed that there is a large increase in circulating gonadotrophin concentrations between Days 30 and 50 of life (YoungLai, 1986), which is several weeks before the rabbit becomes sexually receptive (Hulot et ai, 1982;DeTurckheim et al, 1983;Kamwanja & Hauser, 1983). A similar elevation in gonadotrophin concentrations is seen in the prepubertal female rat before the onset of puberty (Ramaley, 1979).…”
Section: Introductionmentioning
confidence: 96%
“…An interesting aspect of LQT2 is the reversal of TdP risk in pre-pubertal rabbits, before the surge of sex hormones (in 42-day old rabbits)12, 13 where male hearts are more likely to have E4031-induced TdP than female hearts even though females have longer APDs 14. The reversal of TdP-risk in pre-pubertal rabbits is similar in humans where boys (< 14 years old) with inherited LQT2 are more likely to fall victim of lethal arrhythmias than girls 15.…”
Section: Introductionmentioning
confidence: 99%